Mapping of Catchment’s Drainage Networks in Bakri Muar, Johor Using Unmanned Aerial Vehicle - Syaiful, Alfiyandi; Mohd Bukari, Saifullizan (Recent Trends in Civil Engineering and Built Environment, 2022)
Unmanned aerial vehicle technology is no stranger to this era of globalization. The speed of this technological revolution can be used to help with problems that require a quick response. In this study, the problem of floods can be overcome by finding the causes and causes of floods. The study area is focused on the rainwater catchment area in Bukit Bakri, Muar Johor, to be exact along the Sungai Terap which has been hit by floods recently. As a preliminary study, the preparation of information maps such as orthomosaic maps and DEM can help for future studies in flood prevention studies. By applying the latest technology, namely, unmanned aerial vehicles, mapping work can be done with a fast time period and the cost of conducting research is cheaper than traditional methods such as the use of satellites. Taking into account the weather and environmental factors, the raw data in the form of pictures obtained from unmanned aerial vehicles will be processed at the initial stage using the Agisoft Methashape application and further strengthened with additional applications such as QGIS. At the end of this study, an information map in the study area within a will be produced.